DIVERSIFICATION PRODUCTION AND CONSUMPTION OF MORINGA OLEIFERA BECOMING MORINGA LEAF EXTRACT CAPSULES AS AN ALTERNATIVE FOR FOOD RESILIENCE - Asep Budiman; Raden Lucky Radi; Dewi Permata Sari; Nuryanti Taufik (Pasundan International of Community Services Journal (PICS-J), 2022)
Since the occurrence of the COVID-19 pandemic at the end of 2019 until now, the world is threatened with a food crisis, including in Indonesia. The food crisis occurs as a result of the uncertainty of when the pandemic will end. This situation made the Indonesian government start to include food security as a priority program of the government. One of the food security programs declared by the Ministry of Agriculture is the food production and consumption program. Diversification of food production and consumption is the diversification of the types of food consumed and produced with the aim of improving the quality of human resources, developing agriculture in the food sector and improving community nutrition. In this regard, Anaka Village, Kawalu Sub-district is one of the areas in Tasikmalaya that has Moringa farming products, but the community around the plant only uses these agricultural products to make home-cooked food. Therefore, the purpose of this community service program is to provide knowledge and training regarding the production and consumption of Moringa Oleiferainto Moringa leaf extract capsules with the hope that the community will be able to take advantage of the maximum Moringa crop yields and can have business opportunities to generate new sources of income to survive. living in the midst of a food crisis.